2003
DOI: 10.1016/s0167-8655(02)00184-8
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic filtering for model-based segmentation of 4D cylindrical echocardiographic images

Abstract: This paper presents a 4D (3D þ time) echocardiographic image anisotropic filtering and a 3D model-based segmentation system. To improve the extraction of left ventricle boundaries, we rely on two preprocessing stages. First, we apply an anisotropic filter that reduces image noise. This 4D filter takes into account the spatial and temporal nature of echocardiographic images. Second, we adapt the usual gradient filter estimation to the cylindrical geometry of the 3D ultrasound images. The reconstruction of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…An interesting 3D cross-correlation-based approach for speckle tracking on simulated data is proposed in (Chen et al, 2005). Some good examples of temporal segmentation of cardiac US can be found in (Montagnat et al, 2003;Morsy and von Ramm, 1999;Papademetris et al, 2003). Model-based segmentation employing simplex meshes (Montagnat et al, 2003) or finite element models (FEM) (Papademetris et al, 2003) have shown promising results, especially for the left ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting 3D cross-correlation-based approach for speckle tracking on simulated data is proposed in (Chen et al, 2005). Some good examples of temporal segmentation of cardiac US can be found in (Montagnat et al, 2003;Morsy and von Ramm, 1999;Papademetris et al, 2003). Model-based segmentation employing simplex meshes (Montagnat et al, 2003) or finite element models (FEM) (Papademetris et al, 2003) have shown promising results, especially for the left ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…For the external energy, we use a negative gradient norm of 3D ultrasound images preprocessed by 3D anisotropic diffusion [13]. This way we remove the texture information, preserve the contrast, and emphasize the boundaries [4]. To reduce the computational complexity, we discretize the initial contour C t and precompute the B-splines basis function values in the matrix D. We minimize the energy function:…”
Section: Active Contour Segmentationmentioning
confidence: 99%
“…Despite certain advances in technology, 3D ultrasound images are still of low quality with many artifacts, such as attenuation, speckle, shadows, and signal dropout. A relatively small amount of research has been done in motion analysis from 3D echocardiography [3,4,5]. Montagnat and colleagues [4] develop a 3D model-based ultrasound segmentation; the method filters the image by (4D) anisotropic diffusion and fits the LV model to the high intensity gradients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different type of forces may be applied depending on the image modality. We chose to combine intensity and gradient information with a regionbased approach [7] applied to the intensity profile extracted at each vertex in its normal direction. It consists in defining a region with a range of intensity values and then finding its boundary by looking at the voxels of high gradient value.…”
Section: Fig 2 Electromechanical Model In a 4d Ultrasound Imagementioning
confidence: 99%